War, traffic and iatrogenic injuries of D3 duodenal segment - Ignjatović Dragan; Ćuk Vladimir; Mišović Sidor (Vojnosanitetski Pregled, 2005)
Background. Injuries of the duodenum at the level of aortomesenteric clamp (segment D3) are with a high incidence of death due to the development of fistula and peritonitis. In three successfully managed cases, we applied the biliary surgery method. Case reports. All three cases were with the injuries of D3 duodenal segment. The first patient suffered from the blast perforation of duodenum at the level of the aortomesenteric clamp which occurred at the 7th day after the injury. The second patient suffered from the duodenal injury caused in a traffic accident. The third patient suffered from an iatrogenic injury at the beginning of D3 duodenal segment inflicted during ureterolithotomy. The described surgical procedure included basically the suture to narrow the site of the injury, then lateroterminal anastomosis with the Roux-en-Y jejunal flexure and, finally, the placement of a silicone prosthesis starting from the duodenum through the site of injury and the Roux-en-Y out. Octreotide and the total parenteral nutrition were administered to the patients postoperatively. Conclusion. The use of the releasing silicone prosthesis in all three patients provided the repair of the site of the injury with anastomosed Reux-en-Y jejunum.